Understanding teacher identity construction through hybridity theory: a case study of a Chinese-Canadian teaching English in China - Angel Zhao; Yuehai Xiao (Humanities & Social Sciences Communications)
Abstract Globalization has given rise to a new generation of English language teachers, including transnational teachers, who have complex teacher identities that the traditional “native” versus “non-native” English teacher dichotomy fails to capture adequately. Researchers have problematized this dichotomy by applying theories such as poststructuralism. However, there is a lack of consensus on a theory that can challenge the monolingual model and the language hierarchy to support the development of teacher identity. Consequently, this case study draws on the theory of hybridity from sociology and uses narrative inquiry and interviews to explore the evolution of a Chinese-Canadian English teacher, Sally, in constructing her teacher identity, which includes both achievements and challenges. The study contributes to the literature by attempting to lessen the impact of the language hierarchy and the “native” versus “non-native” dichotomy through empirical evidence supporting hybridity theory. The findings reveal the complexity of Sally’s teacher identity development across various contexts, resulting in numerous struggles. This complexity aligns with hybridity theory. Moreover, Sally outlines her coping strategies, which could help transnational teachers overcome obstacles and successfully broaden their teacher identities. The study discusses theoretical and pedagogical implications for the development of English language teacher identity and teacher training.